Companies steer new K-12 courses [education]. - Mcadoo, M. (IEEE spectrum)
While studies show US students still behind their peers abroad in maths and science, efforts to find new ways of teaching show some promising results. After a decade of arms-length aid to US schools, industry is becoming deeply involved in such core school issues as curriculum reform and teaching practices-with some positive results. At issue is a workforce with the technical know-how to keep companies on top of their competitors. The author discusses business-school partnerships, a partnership for teacher training, a partnership for school change, school-to-work opportunities, and apprentice programs